2022
DOI: 10.1002/rrq.463
|View full text |Cite
|
Sign up to set email alerts
|

Online Research and Comprehension Performance Profiles Among Sixth‐Grade Students, Including Those with Reading Difficulties and/or Attention and Executive Function Difficulties

Abstract: This study identified online research and comprehension (ORC) performance profiles of 436 sixth‐grade students (206 girls) aged 12–13 years. We included learner groups with different learning‐related difficulties and explored how students’ reading habits were represented in various performance profiles. First, students’ ORC performance was examined with a validated web‐based assessment measuring their skills in locating, evaluating, synthesizing, and communicating information. Second, reading fluency and teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 123 publications
1
2
0
Order By: Relevance
“…The findings of this study revealed that students in the ETS and ETG groups achieved significant improvement. This finding is consistent with the findings of previous studies, which showed that treatment with certain strategies improves student achievement [3,24,27]. The outstanding achievements of students exposed to ETS and ETG provide opportunities for students to participate and be actively involved in the teaching and learning process.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of this study revealed that students in the ETS and ETG groups achieved significant improvement. This finding is consistent with the findings of previous studies, which showed that treatment with certain strategies improves student achievement [3,24,27]. The outstanding achievements of students exposed to ETS and ETG provide opportunities for students to participate and be actively involved in the teaching and learning process.…”
Section: Discussionsupporting
confidence: 92%
“…Excellent reading comprehension helps students understand a text [1,2]. In addition, strong reading skills requires a supportive environment [3,4], and mastery of reading comprehension on pharmaceutical themes is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…CIL is “an individual's ability to use computers to investigate, create, and communicate in order to participate effectively at home, at school, in the workplace, and in society” (Fraillon et al, 2014, p. xvii). Several international studies have focused on identifying CIL skills, student levels of CIL performance, and related teacher practices (e.g., Bundsgaard & Gerick, 2017; Kanniainen, 2022). The 2018 IEA International Computer and Information Literacy Study defined four levels of information literacy competence, ranging from functional working knowledge of computers at Level 1, to executing evaluative judgment when searching for and creating information at Level 4 (Bundsgaard & Gerick, 2017; Fraillon et al 2014).…”
Section: Conceptual Framework Guiding the Studymentioning
confidence: 99%